2014
DOI: 10.4236/ajac.2014.515109
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Novel Electrochemical Approach to Antioxidant Activity Assay of Metal Porphyrins with Bulky 3,5-Diisobornyl-4-hydroxyphenyl Moieties

Abstract: The complexes of biogenic metals ( )Zn Cu Co Mn Febased on meso-tetra(3,5-diisobornyl-4-hydroxyphenyl)porphyrin 1 were synthesized. The electrochemical behavior of these compounds was studied using cyclic voltammetry (CV) and rotating disk electrode (RDE) techniques. The antioxidant activity of complexes was estimated by means of the electrochemical assay based on the hydrogen atom transfer reaction to the stable radical 2,2'-diphenyl-1-picrylhydrazyl (DPPH). The RDE method was applied for this process monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Recently we proposed the novel approach to monitoring the reaction with DPPH by cyclic voltammetry (CV) and rotating disk electrode (RDE) techniques [34][35][36][37][38]. In [39] this method was successfully applied to study of substituted tetraphenyporphyrines antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we proposed the novel approach to monitoring the reaction with DPPH by cyclic voltammetry (CV) and rotating disk electrode (RDE) techniques [34][35][36][37][38]. In [39] this method was successfully applied to study of substituted tetraphenyporphyrines antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…В большинстве случаев это тетра(мезо-арил)порфирины с четырьмя фенольными фрагментами, непосредственно связан-ными с макроциклом. [8][9][10][11][12][13][14][15][16][17] Как известно, замещенные фенолы относятся к наиболее широко используемым антиоксидантам, эффективность которых возрастает с увеличением числа электронодонорных заместителей, введенных в орто-или пара-положения к ОН-группе. Порфириновый макроцикл также взаимодействует со свободными радикалами.…”
unclassified
“…The obtained antioxidant activity data showed that the aromatic ring bearing electron‐donating substituents increases the antioxidant activity however, electron‐withdrawing substituents decrease it [29] . The higher potency of 6 g as an antioxidant agent may be attributed to the presence of phenolic OH group and strong electron donating t‐butyl groups [30–35] . Similarly, the presence of electron donation OH groups increases the antioxidant activity of 6 h .…”
Section: Pharmacology Of Porphyrinsmentioning
confidence: 94%
“…[29] The higher potency of 6 g as an antioxidant agent may be attributed to the presence of phenolic OH group and strong electron donating tbutyl groups. [30][31][32][33][34][35] Similarly, the presence of electron donation OH groups increases the antioxidant activity of 6 h. Electronwithdrawing substituents as the chlorine atom and nitro group in 6 f, and carboxylic groups in 6 b decrease their antioxidant activity.…”
Section: Structure-activity Relationship (Sar) For the Antioxidant Ac...mentioning
confidence: 99%